Stimulating Awareness and Entrepreneurial Skills of Students through the Strong Role of Social Media: A Motivation for Growth and Innovation - Ruswaji, Ruswaji; Herlina, Nina; Hidayatin, Dina Alafi; Sulaeman, Moh Muklis; Wibowo, Sandi Nasrudin (PT. LITERASI SAINS NUSANTARA, 2024)
Entrepreneurship among students has been a primary focus in the context of the ever-changing global economy. Students are often regarded as potential sources for innovation and economic growth in various countries. This research aims to stimulate awareness and entrepreneurial skills of students through the strong role of social media. In this study, the method employed is a qualitative literature review, drawing data from Google Scholar within the timeframe of 2020 to 2024. The study results indicate that in the rapidly evolving digital era, social media plays a highly significant role in influencing life, including education and entrepreneurship. Social media provides broad access to information, ideas, and opportunities for students. With the right approach, social media can stimulate awareness and develop entrepreneurial skills among students.